Host gill attachment causes blood-feeding by the salmon louse (Lepeophtheirus salmonis) chalimus larvae and alters parasite development and transcriptome - Erna Irene Heggland; Michael Dondrup; Frank Nilsen; Christiane Eichner (Parasites & Vectors, 2020)
Abstract Background Blood-feeding is a common strategy among parasitizing arthropods, including the ectoparasitic salmon louse (Lepeophtheirus salmonis), feeding off its salmon host’s skin and blood. Blood is rich in nutrients, among these iron and heme. These are essential molecules for the louse, yet their oxidative properties render them toxic to cells if not handled appropriately. Blood-feeding might therefore alter parasite gene expression. Methods We infected Atlantic salmon with salmon louse copepodids and sampled the lice in two different experiments at day 10 and 18 post-infestation. Parasite development and presence of host blood in their intestines were determined. Lice of similar instar age sampled from body parts with differential access to blood, namely from gills versus lice from skin epidermis, were analysed for gene expression by RNA-sequencing in samples taken at day 10 for both experiments and at day 18 for one of the experiments. Results We found that lice started feeding on blood when becoming mobile preadults if sitting on the fish body; however, they may initiate blood-feeding at the chalimus I stage if attached to gills. Lice attached to gills develop at a slower rate. By differential expression analysis, we found 355 transcripts elevated in lice sampled from gills and 202 transcripts elevated in lice sampled from skin consistent in all samplings. Genes annotated with “peptidase activity” were among the ones elevated in lice sampled from gills, while in the other group genes annotated with “phosphorylation” and “phosphatase” were pervasive. Transcripts elevated in lice sampled from gills were often genes relatively highly expressed in the louse intestine compared with other tissues, while this was not the case for transcripts elevated in lice sampled from skin. In both groups, more than half of the transcripts were from genes more highly expressed after attachment. Conclusions Gill settlement results in an alteration in gene expression and a premature onset of blood-feeding likely causes the parasite to develop at a slower pace.